New roles for Fc receptors in neurodegeneration-the impact on Immunotherapy for Alzheimer's Disease - Fuller, James P.; Stavenhagen, Jeffrey B.; Teeling, Jessica L. (Frontiers in Neuroscience, 2014)
There are an estimated 18 million Alzheimer’s disease (AD) sufferers worldwide and with no disease modifying treatment currently available, development of new therapies represents an enormous unmet clinical need. AD is characterised by episodic memory loss followed by severe cognitive decline and is associated with many neuropathological changes. AD is characterised by deposits of amyloid beta (Aβ), neurofibrillary tangles, and neuroinflammation. Active immunisation or passive immunisation against Aβ leads to the clearance of deposits in transgenic mice expressing human Aβ. This clearance is associated with reversal of associated cognitive deficits, but these results have failed to translate to humans, with both active and passive immunotherapy failing to improve memory loss. One explanation for these observations is that certain anti-Aβ antibodies mediate damage to the cerebral vasculature limiting the top dose and potentially reducing efficacy. Fc gamma receptors (Fcγ) are a family of immunoglobulin like receptors which bind to the Fc portion of IgG, and mediate the response of effector cells to immune complexes. Data from both mouse and human studies suggest that cross-linking Fc receptors by therapeutic antibodies and the subsequent pro-inflammatory response mediates the vascular side effects seen following immunotherapy. Increasing evidence is emerging that Fc receptor expression on CNS resident cells, including microglia and neurons, is increased during aging and functionally involved in the pathogenesis of age-related neurodegenerative diseases. We propose that increased expression and ligation of Fc receptors in the CNS, either by endogenous IgG or therapeutic antibodies, has the potential to induce vascular damage and exacerbate neurodegeneration. To produce safe and effective immunotherapies for AD and other neurodegenerative diseases it will be vital to understand the role of Fc receptors in the healthy and diseased brain.